PERCEPTION OF ONLINE EVENT TICKET PURCHASING AMONG YOUNG ADULTS IN MALAYSIA (Journal of Event, Tourism and Hospitality Studies, 2023)
Online shopping has ingrained itself within Malaysian society's contemporary lifestyle, with a particular emphasis on its prevalence among young adults. In contrast to traditional purchasing methods, the purchase of event tickets through online channels offers heightened convenience and time efficiency. This advantage stems from the virtual nature of transactions, which effectively caters to consumers with time limitations. Consequently, a noteworthy demographic within Malaysia's online community comprises predominantly of young adults who frequently engage in digital retail practices. Therefore, the main objective of this study is to explore the perceptions of young adults regarding purchasing event tickets online. The study also aims to provide insight on the numerous factors that affect young adults' decision-making processes when it comes to buying event tickets online. To achieve this, a purposive sampling approach was employed, leading to the selection of 150 participants as the study's subjects. The primary data collection method involved the administration of a structured questionnaire, facilitated through a Google Form link, to the selected respondents. The findings of this study show that convenience, trustworthiness, and website usability positively influence online event ticket purchasing among young adults. The outcomes of this initial investigation illuminate the pivotal roles played by convenience, trustworthiness, and website usability in shaping favorable consumer perceptions concerning the acquisition of event tickets through online avenues. Consequently, these findings serve as a foundational framework for e-ticketing service providers to gain insight into customer perceptions and expectations pertaining to the realm of online event ticket transactions. By leveraging this knowledge, the events industry can enhance and refine their online purchasing platforms to better align with consumer preferences and requirements.